Water-soluble and -insoluble biocrude production from hydrothermal liquefaction of microalgae with catalyst. (February 2019) - Xu, Donghai; Guo, Shuwei; Liu, Liang; Wu, Zhiqiang; Wang, Yang; Lin, Guike
Abstract: Hydrothermal liquefaction (HTL) of microalgae produces water-soluble biocrude (WSB) and water-insoluble biocrude (WISB) simultaneously. The effects of heterogeneous catalysts (i.e. Pt/C, Ru/C, Pt/C+Ru/C) on the properties of the two types of biocrudes from Chlorella HTL were explored herein for the first time. The results show that Pt/C was favorable for the production of WISB, and reduced the WSB fraction in WSB+WISB, and obtained the highest C, H contents and the lowest N, O contents in WSB, and led to the highest yield (37.09 wt.%) and energy recovery (71.04%) of total biocrude (WSB+WISB). The WISB produced with Pt/C mainly consisted of amides (48.19%), hydrocarbons (17.68%), organic acids (12.78%), and phenols (7.74%). Pt/C prompted the cracking of high-molecular-weight compounds and the formation of low-boiling-point compounds.